Assessment of by-products of chlorination and photoelectrocatalytic chlorination of an azo dye - Oliveira, Rafael Leite de [UNESP]; Anderson, Marc A.; Umbuzeiro, Gisela de Aragao; Zocolo, Guilherme Juliao [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2012)
The present work describes a more efficient methodology for the chlorination of water containing disperse dyes, where the chlorinated byproducts identified by mass spectra are compared. this investigation, we tested the degradation of Cl Disperse Blue 291 dye, 2-[(2-Bromo-4,6-dinitrophenyl)azo]-5-(diethylamino)-4-methoxyacetanilide) a commercial azo dye with mutagenic properties. The present work evaluates the photoelectrocatalytic efficiency of removing the Cl Disperse Blue 291 dye from a wastewater of the textile industry. We employed NaCl as a supporting electrolyte. It should be noted that photoelectrocatalytic techniques are non-conventional method of generating chlorine radicals. The by-products formed in this process were analyzed using spectrophotometry, liquid chromatography, dissolved organic carbon, mass spectral analysis and mutagenicity assays. The process efficiency was compared with the conventional chlorination process adopted during sewage and effluents treatment processes. This conventional chlorination process is less efficient in removing color, total organic carbon than the photoelectrochemistry technique. Furthermore, we shall demonstrate that the mutagenicity of the generated by-products obtained using photoelectrocatalysis is completely different from that obtained by the conventional oxidation of chloride ions in the drinking wafer treatment process. (C) 2012 Published by Elsevier B.V.
Keywords: Cl Disperse Blue 291; Chlorination of dyes; Removal of azo dye; Phoelectrochemical chlorination; Byproducts of chlorination